Self-medication practice among pregnant and postpartum women attending the regional hospital center of Souss Massa, Morocco: a cross-sectional study - Bouqoufi, Afaf; Lahlou, Laila; Ait El Hadj, Fatima; Boujraf, Said; Abdessadek, Mohammed; Khabbal, Youssef (Frontiers in Pharmacology, 2024)
AB is the principal investigator and a major contributor to all aspects of this study and manuscript; she was involved in study design, study execution, data analysis, critical discussion, and drafting of the manuscript. FA helped in the questionnaire editing and critical discussion. LL contributed greatly to the study design, organized databases, and performed the statistical analysis. SB, MA and YK majorly contributed to critical discussion and revision of the manuscript and helped in study design. All authors read and approved the final version of the manuscript.